Discrete Non‐Linear Sliding Mode‐Based Load Frequency Control Subject to Interval Type‐2 Fuzzy Model - Liu, Xinxin; Gu, Yaxin; Ding, Yu; Zhao, Weiyi (Electronics letters, 2025)
This paper focuses on an adaptive sliding mode‐based load frequency control problem under a memory‐dynamic event‐triggered strategy. First, an interval type‐2 fuzzy model is developed to characterize the discrete‐time load frequency control system. Next, a discrete integral non‐linear sliding mode surface is introduced to eliminate the reaching mode and enhance the robustness of the overall system. Then, an adaptive sliding mode controller is derived to ensure the system's robustness against matched uncertainties and external disturbances, even when the upper bounds are unknown. Finally, simulation results are presented to demonstrate the effectiveness and practical viability of the proposed control technique.